Teaching literacy to learners with dyslexia : a multisensory approach - Kelly, Kathleen S. 4 0 16; (Special needs educator), Phillips, Sylvia; 5 (Los Angeles : SAGE Publications, 2011)
Provides a structured program--including strategies, activities, reproducible resource sheets, and downloadable materials--for teaching literacy skills to children and young people (ages 5 to 18) with dyslexia or specific learning difficulties.
The contribution of theories of causation to the development of a multisensory teaching programme -- The role of memory in acquiring literacy skills -- Phonological skills, literacy and dyslexia -- The development of reading skills -- Spelling development and dyslexia -- Teaching handwriting -- Dyslexia and learners from whom English is an additional language -- Principles, teaching strategies, and programme structure -- Lesson planning -- Alphabet and dictionary work -- Introducing the new teaching point in a lesson -- The role of memory in the programme -- Study skills within the programme -- The Conquering Literacy Programme: examples of activities -- The Accelerated Programme. Conquering Literacy: Accelerated Programme Placement Test ; Conquering Literacy Accelerated Programme Skills Assessment Procedure (CLAPSAP) -- Ideas for working with young children -- Teaching the programme to groups -- Resources.
Includes bibliographical references and indexes.
Keywords: 2 -- 0; 6; Education;Study and teaching;Education -- Dyslexic children;Literacy;Learning disabled children -- Great Britain.;Great Britain.;Great Britain. -- 20; 20; 2